Pengaruh Sistem Informasi Akuntansi Penjualan, Penerimaan Kas dan Pengeluaran Kas Terhadap Pengendalian Internal - Lidia Margaretta Purba; Cris Kuntadi; Rachmat Pramukty (Madani: Jurnal Ilmiah Multidisiplin, 2023)
In research or scientific articles, previous or relevant research is very important because it helps strengthen theories and phenomena of the relationship or influence between variables. In this article, the literature on Accounting Information Systems discusses the components that influence Internal Control, including Accounting Information Systems for Sales, Cash Receipts, and Cash Disbursements. Building a hypothesis of influence between variables is the aim of this paper. The results of this literature research are as follows: 1) Sales Accounting Information Systems affect Internal Control; 2) Cash Receipts Accounting Information System affects Internal Control; and 3) Cash Disbursement Accounting Information System affects Internal Control.Â